IMMUNOPHENOTYPING OF PLASMA CELL AND THE UTILITY OF FLOW CYTOMETRY IN PLASMA CELL DYSCRASIAS. (February 2015) - Tran, Daniel; Smith, Sandy; Brown, David; Sewell, William
Abstract : Aims: To prospectively compare the performance of CD27/CD28/CD81/CD117/CD126/CD147/CD152/CD200/CD229 to current markers (gating- CD38/CD138/CD45; clonality- κ-/λ-light chain; phenotype- CD19/CD56) to assess utility in identifying neoplastic plasma cells (PC) and distinguishing monoclonal gammopathy of unknown significance (MGUS) and multiple myeloma (MM). To retrospectively assess polychromatic flow cytometry's (PFC) contribution to diagnosing plasma cell dyscrasias through correlation with other investigations. Methods: Antibody panels including new markers (CD27/CD28/CD81/CD117/CD126/CD147/CD152/CD200/CD229) were run on BM samples. Database analysis of bone marrow samples at St Vincent's hospital was conducted to correlate PFC with other investigations. Results: CD19 and CD19/CD147 were the best single marker and 2-marker combination respectively for identifying monoclonals. CD229 was best at differentiating MM and MGUS, and additional markers did not improve differentiation. PFC correlated with electrophoresis, cytogenetics and imaging. PFC detected 29 monoclonal cases that trephine analysis classified as polyclonal. These cases had low PC numbers and polyclonal PC backgrounds. Conclusion: CD19/CD147 could be more useful than CD19/CD56 in distinguishing monoclonal and polyclonal populations. CD229 may help PFC differentiate MM from MGUS. Despite PFC's underestimation of PCs, PFC correlates with other investigations and may be particularly useful in minimal residual disease where small PC populations occur or where background reactive plasmacytosis occurs.